Recent advances in the synthesis of plakortin-type polyketides. Issue 46 (13th November 2020) - Li, Qingong; Yang, Hongzhi; Tang, Yefeng
Abstract : The recent progress in the synthesis of plakortin-type polyketides is summarized, with an emphasis on the key elements enabling rapid assembly of the polycyclic cores of chased targets. Abstract : Plakortin-type polyketides represent a growing family of sponge-derived marine natural products that display notable structural and biological diversity. In particular, a series of polycyclic plakortin polyketides, namely hippolachnin A and gracilioethers, have been identified in recent years, which attract immense interest from the synthetic community owing to their unique molecular architectures and promising biomedical potential. A number of elegant total syntheses of these targets and some synthetic studies have been performed through either bio-inspired or rationally designed strategies. This focused review aims to provide an up-to-date summary of the progress in the chemical synthesis of plakortin polyketides, with an emphasis on the key synthetic elements enabling the rapid assembly of their core skeletons.